Effect of the microstructure on the crack initiation during thermal cycling of Nb–Ti-bearing continuous casting slabs. (21st April 2021) - Zeng, Ya-Nan; Feng, Qian; Li, Jun-Guo; Wang, Ya-Jun; Tang, Guo-Zhang
ABSTRACT: To discussed the influence of reheating and cooling on the crack initiation mechanism under the hot cycle mode of a continuous casting slab, during thermal cycling and analysed the relationship between the lower grain size and the crack initiation toughness under different temperature fluctuations. A thermal expansion tester and a Gleeble-3500 thermodynamical simulator were used to perform thermal processing experiments on the samples, where in the temperature fluctuations during solidification were 25 K, 50 K, and 75 K. Scanning electron microscopy (SEM), optical microscopy (OM) and other characterization methods were used to analyse the morphology, microstructure, thermoplasticity and residual stress of the cracked tensile test samples, which were taken from the Nb-Ti-bearing slabs. The result shows that with the intensification of the temperature-returning process, the grain size at the fracture and the size of the slab fracture toughness are increases, which leading to a decrease in crack initiation toughness.